Program Kerja Rumah Pintar dalam Mengembangkan Literasi Budaya Anak Usia Sekolah Dasar di Yayasan Fajar Sejahtera Indonesia (YAFSI) Kelurahan Amplas - Adha Rahimi; Abdul Karim Batubara; Muslih Fathurrahman (Universitas Palangka Raya, 2024)
This research was conducted at the Smart House of the Fajar Sejahtera Indonesia Foundation (YAFSI) in Amplas Village. The study aimed to determine the efforts of volunteers in developing cultural literacy programs at the Smart House of the Fajar Sejahtera Indonesia Foundation (YAFSI) in Amplas Village, to identify the factors causing the low implementation of the Smart House's work program in developing cultural literacy for elementary school children at the Fajar Sejahtera Indonesia Foundation (YAFSI) in Amplas Village, and to assess the impact and benefits of the Smart House program on children and the community. In conducting this research, the researcher chose qualitative research with a descriptive approach. To obtain data, the researcher used interview, observation, and documentation techniques. Triangulation of sources technique was employed to test the validity of the data. The results of this study showed that: 1). The efforts of volunteers in developing cultural literacy work programs have been well-implemented, such as providing understanding and strengthening of cultural literacy, the availability of adequate literacy facilities, and collaboration with other organizational institutions. 2). There are several factors that cause the low implementation of the work program, including the lack of awareness or concern among children about information development related to cultural literacy, limited facilities such as reading materials, mutual understanding, and low interest and motivation among children. Therefore, the presence of the Smart House program aims to direct children to continue developing various literacy activities, especially cultural literacy. Given this, the YAFSI Smart House volunteers have introduced various positive and creative work programs to advance cultural literacy development, such as traditional dance activities, storytelling, singing, reading, and more. 3). The impact and benefits provided by the YAFSI Smart House program include children becoming character-based peer educators, having high literacy attitudes, and implementing various activities reflecting cultural literacy development. The impact and benefits for the community include the ability to transform the community to advance in building businesses and entrepreneurship based on local potential.